Findings of the safety inspections found on the TEN-T road network in the Czech Republic - Carsky, Jiri; Johanidesova, Adela; Kocourek, Josef (International Journal of Integrated Engineering, 2018)
In 2015 the Czech Technical University in Prague carried out a safety inspection on the TEN-T road network in the Czech Republic and on the selected 1st class roads (in the future they are intended to replace the planned TEN-T network). This article is designed to provide a basic overview of the most common problems in terms of both the frequency with which these risks occur and their significance. This article will also present a newly developed web application, CEBASS, which gives road operators an effective and systematic tool to manage the process of solving these problems. The aim of this article is to describe the classification created and used during the safety inspection course, which is better for road operators than the existing methods for safety inspections.